The effect of the case-based learning approach on the level of satisfactions and learning of nursing students in Iran: A randomized controlled trial - Farzaneh Arab; Maryam Saeedi (Heliyon, 2024)
Introduction: Nurses must have sufficient knowledge and skills in the field of medications and medication management. This study was designed to investigate the effect of the case-based learning (CBL) approach on the level of satisfaction and learning of nursing students. Materials and methods: This study was conducted using a randomized controlled trial on 70 Iranian third-semester nursing students during a pharmacology internship in 2023. After considering the inclusion criteria, the samples were entered into the study by census method and then they were placed in either the control (35 people) or intervention (35 people) groups by simple random method. Pharmacology training was done in the control group by the usual method (lectures by the instructor and conferences with students) and in the intervention group by the Kaddoura case-based learning method. Data collection tools included a demographic questionnaire, satisfaction of educational approach questionnaire, and exam scores before and after the internship. SPSS version 26 software was used for statistical analysis. Results: There was no statistically significant difference (P = 0.88) in the mean scores of the pharmacology pre-test in the control (10.54 ± 2.74) and intervention groups (10.6 ± 3.49) before the intervention. Also, there was no statistically significant difference (P = 0.19) between the pharmacology post-test scores in the control (17.7 ± 1.15) and intervention groups (18.07 ± 0.91). A comparison of pre-test and post-test scores in both control and intervention groups showed that the post-test scores in both groups increased significantly (P < 0.001). The results showed that the intervention group was significantly (P = 0.008) more satisfied with the learning method. Conclusion: The case-based educational approach resulted in improved satisfaction among students in the pharmacology course. It is recommended to incorporate this learning method alongside traditional teaching methods, in nursing education, particularly in pharmacology instruction.